Biological adhesives: from biology to biomimetics - Flammang, Patrick (2020)
Biological adhesives offer impressive performances and, therewith, the potential to inspire novel, more reliable, efficient and environmentally friendly adhesives for an increasing variety of applications. Adhesives found in nature do indeed perform in ways that man-made products simply cannot match. Some are reversible, others work most effectively underwater and many are universal in their performance to substrates of varying composition and structure. No wonder then that of all biological phenomena that have been investigated with a biomimetic purpose, bioadhesion has perhaps received the most interest. However, our knowledge of natural adhesive systems remains distant from the engineering of innovative adhesives for specific industrial needs. It is necessary therefore to understand the mode of action of biological adhesives and to elucidate their basic components, building principles and function-specific adaptations selected by evolution. It is this challenge that has been at the origin of the creation of a network of researchers under the auspices of COST, the European Cooperation in Science and Technology. This so-called COST Action1 ran from 2010 to 2014, and its main objective was the identification of potentially interesting biological adhesives and their functional characterization, so as to facilitate the development of synthetic counterparts with improved function. The series of papers presented in this theme issue stem from the collaborative works conducted within the framework of this COST Action.